Special issue of the Journal of Electrocardiology to commemorate Dr. Galen Wagner (1939–2016) - Atwater, Brett D.; Bacharova, Ljuba; Pahlm, Olle; Swenne, Cees A. (Journal of electrocardiology, 2017)
Galen Wagner, MD, the Editor-in-Chief of this Journal, passed away on July 13, 2016. He served the Journal for almost 12 years. The Editorial Board considers it appropriate to open the 50th volume of the Journal with six contributions which commemorate Dr. Wagner: